Effect of ultra-low temperature on some mechanical properties of painted and film-coated plywood - Mustafa Oncel; Osman Emre Ozkan (Universidad del Bio Bio, 2023)
Plywood is used for insulation systems in liquid natural gas cargo ships because of its good thermal properties. However, there are only a few research investigating the mechanical properties of plywood exposed to ultra-low temperatures. This study aims to determine how plywood reacts when exposed to ultra-low temperatures, such as - 196 °C. To achieve this purpose, the present study investigated the bending strength, modulus of elasticity, and tensile-shear strength of painted and film-coated plywood under ultra-low temperatures. The mechanical properties of plywood were discovered to be significantly impacted by the ultra-low temperature as a result of this research.. Moreover, not only the bending strength of the painted and film-coated plywood increased with decreasing temperature, but also the modules of elasticity of the painted and film-coated plywood increased. At decreasing temperature, the tensile shear strength of the painted and film-coated oven-dried plywood increased, but the ensile-shear strength of painted and film-coated air-dried plywood decreased. The tensile shear strength of air-dried plywood was determined to be more sensitive to the temperature change. Therefore, attention should be paid to plywood used in liquefied natural gas cargo ships with high humidity.
Keywords: Bending; Birch; Manufactures; modulus of elasticity; Forestry; tensile shear strength; SD1-669.5; TS1-2301; plywood; 7. Clean energy